Prevalencia de Toxoplasmosis en Caninos Domésticos (canis familiaris) en la Parroquia La Matriz, Cantòn Latacunga. - Criollo Cordones, Katherin Cristina (2018)
The present study of investigation have with objective decide the prevalence of Toxoplasmosis in domestic canines in the parish the Matriz of the canton Latacunga, in the present year Two thousand and eighteen, It has been made Ninety-four study units (hundred percent of the domestic canines of the sector) chosen indiscriminately in relation to their sex, age and race. She was extracted three milligrams of blood from the radial vein or jugular vein of canines, allowing so under the process of centrifuged get the amount of serum required, to measure immunoglobulin’s of toxoplasmosis IgG/IgM through of the exam hematological and through the (kit toxoplasmosis indirect multi-species) that were processed in the laboratory of Agrocalidad of Quito – Tumbaco, obtaining the following results: The absolute prevalence of toxoplasmosis in domestic canines of the Matriz parish is 40.43% of a total of 94% study units, giving positive to the test, to the prevalence by ages the results are: in canines of 0-12 months 47.2%, 1-5 years 34.8% and> 5 years of 50%. While the prevalence by races predominates with Mestizos 44.1%, Pastor Aleman 50%, Poodle 50%, Shar Pei 50%, Doberman Pinscher 100%, French Poodle 20%, Schnauzer 33.3%, Husky 100%, Golden 50%, taking into account that the prevalence by sex in males was 38.5% and in females 43.2%, those results were socialized to the owners of the domestic canines, of the parish of Matriz, Afterwards, an instruction manual for the management, control, hygiene and prevention of toxoplasmosis in domestic canines was delivered.